Reactivity in Economic Science - Bruno S. Frey (Center for Research in Economics, Management and the Arts (CREMA), 2017)
There is a fundamental difference between the natural and the social sciences due to reactivity. This difference remains even in the age of Artificially Intelligent Learning Machines and Big Data. Many academic economists take it as a matter of course that economics should become a natural science. Such a characterization misses an essential aspect of a social science, namely reactivity, i.e. human beings systematically respond to economic data, and in particular to interventions by economic policy, in a foreseeable way. To illustrate this finding, I use three examples from quite different fields: Happiness policy, World Heritage policy, and Science policy.
Keywords: A10; B40; C70; C80; D80; Z10; 330; Economics; Social; Natural Science; Reactivity; Data; Happiness; Economic Policy